Doctoral supervisors and PhD students' perceptions about the supervision process in a young European university - Ribau, Isabel (2021)
In the last decade with the Bologna implementation, doctoral supervision gained a new emphasis and emerged as crucial for developing the European research area. Research, on doctoral supervision practices, and the supervisor ideal profile was carried out in a TOP 10 young European university, at Universidade Nova de Lisboa. The results show that meetings (individual or in groups) are the most implemented practice. Usually, students present orally, to a supervisor, the research that they already made regarding the initial work plane. Two supervisors’ profiles emerge from the students’ voices, the real and the ideal. The ideal supervisor profile that emerges from the questionnaires features supervisors who take students care, give feedback on work on time, and are honest and critical.